Faktor-faktor yang mempengaruhi kinerja pemerintah daerah - Triwulandari, Erika; Pratiwi, Desy Nur; Darmanto, Darmanto (Journal of Accounting and Digital Finance, 2022)
Regional financial management is entirely in the hands of the local government so that it will show the resulting performance. This study aims to determine the factors influencing local government performance in the Boyolali District SKPD for 2021. The sampling method was purposive, with a total sample of 80 respondents. This study uses multiple linear regression. The results of this study show that the implementation of the regional financial accounting system does not affect the performance of local governments in the Boyolali Regency. In contrast, regional financial management and organizational commitment significantly positively affect local government performance in the Boyolali Regency.